2020
DOI: 10.1155/2020/7150605
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moxibustion on the Serum Levels of MMP‐1, MMP‐3, and VEGF in Patients with Rheumatoid Arthritis

Abstract: Background. Rheumatoid arthritis (RA) is a chronic inflammatory autoimmune disease, which will eventually lead to joints deformity and functional damage. The aim of this research is to evaluate the effect of moxibustion on the serum indicators related to bone and cartilage metabolism, matrix metalloproteinase 1 (MMP-1), matrix metalloproteinase 3 (MMP-3), and vascular endothelial growth factor (VEGF) in patients with RA and to explore the mechanism of moxibustion in the treatment of RA. Methods. We recruited 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 34 publications
3
12
0
Order By: Relevance
“…e results of our study showed that, under standard treatment, the values of RAI, SJC, DAS28, and SF-MPQP in the two groups were significantly decreased, which objectively reflected that the symptoms of joint swelling and pain and disease activity of the patients were significantly improved, and the improvement degree in the treatment group with moxibustion was more significant. is result is basically consistent with our previous research results [20,21], which all prove that moxibustion therapy combined with western medicine can improve the curative effect to a greater extent, improve the clinical symptoms of patients, and reduce the pain of patients.…”
Section: E Efficacy Of Moxibustion Joint Swelling and Painsupporting
confidence: 92%
See 4 more Smart Citations
“…e results of our study showed that, under standard treatment, the values of RAI, SJC, DAS28, and SF-MPQP in the two groups were significantly decreased, which objectively reflected that the symptoms of joint swelling and pain and disease activity of the patients were significantly improved, and the improvement degree in the treatment group with moxibustion was more significant. is result is basically consistent with our previous research results [20,21], which all prove that moxibustion therapy combined with western medicine can improve the curative effect to a greater extent, improve the clinical symptoms of patients, and reduce the pain of patients.…”
Section: E Efficacy Of Moxibustion Joint Swelling and Painsupporting
confidence: 92%
“…In our previous study, it was found that the contents of inflammatory factors dominated by IL-1β and TNF-α in serum of RA patients treated with moxibustion decreased significantly, which was also fully reflected in this study [20,21]. It is worth noting that, in this study, the CXCL1 content in patient serum of the treatment group was significantly decreased, and it was significantly positively correlated with the improvement of IL-1β and TNF-α.…”
Section: Effects Of Moxibustion On the Contents Of Cxcl1 β-Ep Tnf-α And Il-1β In Ra Patientssupporting
confidence: 79%
See 3 more Smart Citations